Caregiving burden, depression, and anxiety among family caregivers of patients with cancer: An investigation of patient and caregiver factors - Karimi Moghaddam, Zhaleh; Rostami, Mina; Zeraatchi, Alireza; Mohammadi Bytamar, Jahangir; Saed, Omid; Zenozian, Saeedeh (Frontiers in Psychology, 2023)
Background: Evidence on the caregiving burden and its inevitable consequences is limited. Caring for cancer patients is such a huge burden on their families and in a long time can lead to changes in their mental and physical well-being. This study aimed at determining the prevalence of caregiving burden, depression, and anxiety with a focus on the patient and caregiver-related factors among cancer family caregivers. Methods: A cross-sectional study was conducted on the population of caregivers of adult cancer patients in Zanjan, Iran between 2019 and 2020. Beck Depression Inventory, Beck Anxiety Inventory, and Zarit burden inventory were used to measure outcome variables. Clinical and basic characteristics of the caregivers and their patients were also gathered using a questionnaire designed for this purpose. Independent samples t-test, Analysis of Variance, Pearson’s correlation coefficient and stepwise linear regression were performed using SPSS v.26 to analyze data. Results: Mean ± SD age of the caregivers (167 male and 133 female) was 40.77 ± 12.56. 46.3% of the caregivers showed severe depression. Also, 53% represented severe anxiety. Severe burden (30.7%) was the most frequent category. Duration of caregiving (≥24 months), care setting (outpatient), employment status (retired), depression, health insurance (supplemental), education (illiterate), type of treatment (surgery), ECOG (1), and patients’ age were found to be predictors of caregiving burden. Conclusion: High levels of depression, anxiety and burden were observed among the caregivers of cancer patients. These findings underline the importance of paying close attention to the needs and psychological challenges of this population.